2016
DOI: 10.1371/journal.pone.0155292
|View full text |Cite
|
Sign up to set email alerts
|

Rac1 Activation Caused by Membrane Translocation of a Guanine Nucleotide Exchange Factor in Akt2-Mediated Insulin Signaling in Mouse Skeletal Muscle

Abstract: Insulin-stimulated glucose uptake in skeletal muscle is mediated by the glucose transporter GLUT4, which is translocated to the plasma membrane following insulin stimulation. Several lines of evidence suggested that the protein kinase Akt2 plays a key role in this insulin action. The small GTPase Rac1 has also been implicated as a regulator of insulin-stimulated GLUT4 translocation, acting downstream of Akt2. However, the mechanisms whereby Akt2 regulates Rac1 activity remain obscure. The guanine nucleotide ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(50 citation statements)
references
References 45 publications
2
48
0
Order By: Relevance
“…Plasmid DNAs and siRNAs were introduced into mouse gastrocnemius muscle by electroporation as previously described [16]. Adult male C57BL/6 mice were anesthetized by intraperitoneal injection of a solution of medetomidine (0.3 mg/kg of body weight), midazolam (4.0 mg/kg of body weight), and butorphanol (5.0 mg/kg of body weight).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Plasmid DNAs and siRNAs were introduced into mouse gastrocnemius muscle by electroporation as previously described [16]. Adult male C57BL/6 mice were anesthetized by intraperitoneal injection of a solution of medetomidine (0.3 mg/kg of body weight), midazolam (4.0 mg/kg of body weight), and butorphanol (5.0 mg/kg of body weight).…”
Section: Methodsmentioning
confidence: 99%
“…A constitutively activated mutant of FLJ00068 indeed stimulated GLUT4 translocation in skeletal muscle of wild-type, but not m-rac1-KO, mice [15]. Moreover, Rac1 activation and GLUT4 translocation caused by ectopic expression of a constitutively activated mutant of PI3K or Akt2 were completely abrogated by small interfering RNA (siRNA)-mediated knockdown of FLJ00068 in mouse skeletal muscle [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent paper shows in an inducible skeletal muscle-specific Rac1 KO mouse the requirement for Rac1 in exercise-induced GLUT4 translocation ( 76 ). Although most evidence shows independent activation of Rac1 and Akt downstream of PI3K, there are reports of AKT2 regulating Rac1 activity to impact GLUT4 translocation in skeletal muscle cells ( 77 , 78 ), involving the guanine nucleotide exchange factor FLJ00068 ( 79 , 80 ). Rac1 superactivation has also been shown to activate AKT to trigger induce GLUT4 translocation in a manner independent of insulin ( 81 ).…”
Section: The New Rac1-p21-activated Kinase 1 (Pak1)-actin Remodeling mentioning
confidence: 99%
“…Without prenylation, the small GTPases are unable to anchor to the cell membrane [33]. Recent studies revealed that Rac1, belonging to the family of Rho GTPases, governs the glucose uptake through regulation of GLUT4 translocation both in response to insulin or to exercise in vivo [3434,35]. Our studies indicate that the impairment of glucose uptake in response to insulin after treatment with simvastatin may be associated with the lack of Rac1active form.…”
Section: Simvastatin Inhibited Rac1 Activity In C2c12 Myotubesmentioning
confidence: 71%